Fragmentation of Self and Identity in Samrawyat (brown-skinned women) Novel: A Cultural Critique Perspective - الأحمدي أسماء مقبل عوض (Arts for Linguistic & Literary Studies, 2021)
This study examines fragmentation of self and identity in Samrawyat, the novel which was written by the Eritrean novelist Hejji Jaber and published in (1976). The novel focuses on the dialectics of alienation and belonging and the swinging of the main character between the past and present in search of missing identity. It also explores the manifestations of fragmentation and division of the self and its attempt to bridge the gap in its memory. The study is divided into five parts: alienation versus belonging, fragmentation and self-division, search for self and identity, artistic construction, consolidation of fragmentation, and title fragmentation. Based on the cultural critique approach, the novelist fully embraces a philosophy of renewal in the narrative technique, plot construction, and shift of settings. Fragmentation is seen as central to adopting this philosophy and artistic creation. The novel is considered a model for Arabic narrative innovation in form and content, as it uses the idea of dispersion to reflect the psychological state of the narrator and the fragmentation he experiences between the past and present and between Jeddah and Asmara.